QCD thermodynamics with Wilson quarks - Bitar, K; Edwards, R; Heller, U; Kennedy, A; DeGrand, T; Gottlieb, S; Krasnitz, A; Kogut, J; Renken, R; Liu, C; Rossi, P; Ogilvie, M; et al. (1991)
We present results from a study of hadron thermodynamics with Wilson quarks. The crossover curve between the high and low temperature phases is determined as a function of the gauge coupling and hopping parameter on 83 × 4 lattices. Meson masses are calculated along the crossover curve, and screening lengths are determined in the vicinity of it on 83 × 16 and 82 × 16 × 4 lattices, respectively. © 1991.